2017
DOI: 10.3390/buildings7040120
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Waste Water from a Concrete Plant in the Production of Cement Composites

Abstract: This article presents the results of a study dealing with the utilization of sludge water from a concrete plant as a partial replacement for mixing water in the production of cement composites. The replacement of mixing water with sludge water from a concrete plant was carried out in the amounts of 20% and 50%. The following tests were carried out in order to determine the effect of the replacement of mixing water with sludge water from a concrete plant on the physical and mechanical properties of the cement c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…Based on the raw WWW electrical conductivity (Ec) (11,854 µS/cm) and the total dissolved salts (TDS) (7097 mg/L), it can be classified as high saline brackish waste water. Klus et al [13] reported that the raw waste water from a ready mix concrete plant has a pH value of 12.5 and Ec of 13,390 µS/cm, indicating the results presented here were consistent with previous research. The high pH was mainly attributed to the dissolved alkali hydroxides such as Ca(OH) 2 , Mg(OH) 2 , NaOH, and KOH.…”
Section: Chemical and Physical Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the raw WWW electrical conductivity (Ec) (11,854 µS/cm) and the total dissolved salts (TDS) (7097 mg/L), it can be classified as high saline brackish waste water. Klus et al [13] reported that the raw waste water from a ready mix concrete plant has a pH value of 12.5 and Ec of 13,390 µS/cm, indicating the results presented here were consistent with previous research. The high pH was mainly attributed to the dissolved alkali hydroxides such as Ca(OH) 2 , Mg(OH) 2 , NaOH, and KOH.…”
Section: Chemical and Physical Propertiessupporting
confidence: 92%
“…Previous studies have shown promising results regarding the recycling of ready-mixed concrete waste water in several ratios with fresh water for concrete production [11,12]. Klus et al [13] reported that recycling the waste water from concrete plant as partial replacement of mixing water (20%, 50%) in mortar production is possible without harmfully affecting the mechanical properties. The results revealed that using WWW led to a 15 min reduction in the setting time and increased the flexural strength as well as the compressive strength at 28 days of age.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The existing final filtrate still has high turbidity and high COD, polluting the surrounding mangrove areas. In fact, this water still can be processed further to be reused for washing vehicles transporting liquid concrete, for domestic use in bathrooms and toilets, even as processing water (Chen et al, 2020Klus et al, 2017;Ekolu & Dawneerangen, 2010)…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…24 For special contaminants, they can also be bound by chemical actions through formation of insoluble complexes or hydroxides in alkaline environment, 25 ion exchange between wastes and crystalline phases, 26,27 or ion integration in defects of amorphous products. 28,29 Though having an effective solidication, it usually takes several hours for cement to set to solidify wastes, 30,31 and may be even longer when some types of wastes inhibit cement reacting with water. [32][33][34] Therefore, cementitious solidication method sometimes is hard to be considered as a time-efficient technique and is difficult to achieve rapid solidication when emergencies occur.…”
Section: Introductionmentioning
confidence: 99%